Modulation of Retrograde Trafficking of KCa3.1 in a Polarized Epithelium - Lee, Bob Shih-Liang; Devor, Daniel C.; Hamilton, Kirk L. (Frontiers in Physiology, 2017)
In epithelia, the intermediate conductance, Ca2+-activated K+ channel (KCa3.1) is targeted to the basolateral membrane (BLM) where this channel plays numerous roles in absorption and secretion. A growing body of research suggests that the membrane resident population of KCa3.1 may be critical in clinical manifestation of diseases. In this study, we investigated the key molecular components that regulate the degradation of KCa3.1 using a Fisher rat thyroid cell line stably expressing KCa3.1. Using immunoblot, Ussing chamber and pharmacological approaches, we demonstrated that KCa3.1 is targeted exclusively to the BLM, provided a complete time course of degradation of KCa3.1 and degradation time courses of the channel in the presence of pharmacological inhibitors of ubiquitylation and deubiquitylation to advance our understanding of the retrograde trafficking of KCa3.1. We provide a complete degradation profile of KCa3.1 and that the degradation is via an ubiquitin-dependent pathway. Inhibition of E1 ubiquitin activating enzyme by UBEI-41 crippled the ability of the cells to internalize the channel, shown by the increased BLM surface expression resulting in an increased function of the channel as measured by a DCEBIO sensitive K+ current. Additionally, the involvement of deubiquitylases and degradation by the lysosome were also confirmed by treating the cells with PR-619 or leupeptin/pepstatin, respectively; which significantly decreased the degradation rate of membrane KCa3.1. Additionally, we provided the first evidence that KCa3.1 channels were not deubiquitylated at the BLM. These data further define the retrograde trafficking of KCa3.1, and may provide an avenue for therapeutic approach for treatment of disease.